2018
DOI: 10.5114/aoms.2016.59508
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ketamine and thiopental used alone or in combination on the brain, heart, and bronchial tissues of rats

Abstract: IntroductionWe compared the side effects of ketamine and thiopental used alone and of a ketamine/thiopental combination dose on the brain,heart, and bronchial tissues of rats.Material and methodsThree groups received intraperitoneal injections of 30 mg/kg ketamine (K-30); 15 mg/kg thiopental (T-15); or of both in combination (KTSA). These doses were doubled in another set of study groups (K-60, T-30, and KTA groups, respectively). Optimal anesthesia duration was examined in all groups.ResultsAnesthesia did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…At the end of the treatment, the rats were deprived of food all night. Then, they were weighed and sacrificed after anaesthesia to the thiopental (30 mg/kg) for the collection of the testes, epididymis, seminal vesicle and prostate gland (Ahiskalioglu et al., 2018). These reproductive organs were cleaned of adherent tissue, weighed and rinsed with physiological water.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the treatment, the rats were deprived of food all night. Then, they were weighed and sacrificed after anaesthesia to the thiopental (30 mg/kg) for the collection of the testes, epididymis, seminal vesicle and prostate gland (Ahiskalioglu et al., 2018). These reproductive organs were cleaned of adherent tissue, weighed and rinsed with physiological water.…”
Section: Methodsmentioning
confidence: 99%
“…51 Thiopental was purchased from EIPICO. It was used for anaesthesia in a dose of 30 mg/kg × bw ip, 52 before BLM instillation. ATRA was purchased from Thermo Fisher.…”
Section: Chemicalsmentioning
confidence: 99%
“…In rats with spinal cord contusion injury it showed beneficial effects, because spinal cord MDA was significantly lower than in control rats not treated with thiopental ( 25 ). In another study ( 44 ), in contrast, rats showed higher MDA and lower GSH, GPx, and GSHR levels in brain, heart, and bronchial tissues. In dogs with surgical trauma thiopental significantly increased plasma TOS, while TAS remained unchanged, which resulted with increased OSI ( 31 ).…”
Section: Intravenous Anaestheticsmentioning
confidence: 89%
“…In fact, ketamine anaesthesia resulted in significantly lower kidney and liver tissue MDA than propofol, thiopental, and fentanyl ( 28 , 48 ). In another study ( 44 ), the authors attributed significantly higher MDA and lower GSHR and GPx levels to ketamine-triggered boost of adrenaline, which is known to induce oxidative stress ( 49 ). In mice, ketamine also turned out to mitigate (secondary) brain injury which occurs when ROS production overwhelms the antioxidant system ( 50 ).…”
Section: Intravenous Anaestheticsmentioning
confidence: 99%